Redox-responsive core cross-linked prodrug micelles prepared by click chemistry for pH-triggered doxorubicin delivery - X. T. Cao; C. M. Q. Le; H. H. P. Thi; G-D. Kim; Y-S. Gal; K. T. Lim (eXPRESS Polymer Letters)
A pH-triggered drug delivery system of degradable core cross-linked (CCL) prodrug micelles was prepared by click chemistry. Doxorubicin conjugated block copolymers of azido functional poly(ethylene oxide)-b-poly(glycidyl methacrylate) were synthesized by the combination of RAFT polymerization, epoxide ring-opening reaction, and acid-cleavable hydrazone linkages. The CCL prodrug micelles were produced by the reaction of dipropargyl 3,3′-dithiodipropionate and dipropargyl adipate cross-linking agents with the azido groups of the micellar core via alkyne-azide click reaction, which were denoted as CCL/SS and CCL/noSS, respectively. The TEM images of CCL/SS prodrug micelles showed a spherical shape with the average diameter of 61.0 nm from water, and the shape was maintained with an increased diameter upon dilution with 5-fold DMF. The high DOX conjugation efficiency was 88.4%. In contrast to a very slow DOX release from CCL/SS prodrug micelles under the physiological condition (pH 7.4), the drug release is much faster (90%) at pH 5.0 and 10 mM of GSH after 96 h. The cytotoxicity test and confocal laser scanning microscopy analysis revealed that CCL/SS prodrug micelles had much enhanced intracellular drug release capability in HepG2 cells than CCL/noSS prodrug micelles.